Pilot judgment of the ECtHR on inhuman and degrading treatment in European prisons - Turturro Pérez de los Cobos, Sara (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
The prohibition of torture and inhuman and degrading treatment is absolute and is present in all human rights treaties and conventions. However, in some European prisons there is a systematic violation of article 3 of the European Convention on Human Rights (ECHR). The European Court of Human Rights uses the pilot judgment procedure to impose on the States the adoption of general measures to put an end to a systemic or structural problem. In this article I will explain the pilot judgment procedure and I will analyze the pilot judgments on prison conditions. The main objective is to determine whether pilot sentences are a useful instrument to improve the effectiveness of article 3 of the ECHR.
Keywords: European Court of Human Rights; pilot judgment; prison overcrowding; prisons; prison conditions; prohibition of torture; article 3 of the European Convention of Human Rights